‘Callide’ Rhodesgrass - Joao Vendramini; Ann Blount; Yoana Newman; C. G. Chambliss; Martin B. Adjei (EDIS)
Revised! SS-AGR-59, a 4-page fact sheet by J. Vendramini, A. Blount, Y. Newman, C. G. Chambliss, and M. B. Adjei, describes this robust, warm-season perennial grass native from Africa, useful in southern Florida for fall and winter grazing — establishment, management of established stands, and pests. Includes references. Published by the UF Department of Agronomy, March 2010.